WHO Expert Committee on specifications for pharmaceutical preparations : forty-seventh report (Geneva, Switzerland : World Health Organization, 2013)
The Expert Committee on Specificatins for Pharmaceutical Preparatins works towards clear, independent and practical standards and guidelines for the quality assurance of medicines.
Introduction -- General policy -- Quality control: specifications and tests -- Quality control: international reference materials (International Chemical Reference Substances and International Infrared Reference Spectra) -- Quality control: national laboratories -- Quality assurance: good manufacturing practices -- Quality assurance: new approaches -- Quality assurance: distribution and trade of pharmaceuticals -- Prequalification of priority essential medicines including active pharmaceutical ingredients -- Prequalification of active pharmaceutical ingredients -- Prequalification of quality control laboratories -- Regulatory guidance -- Nomenclature, terminology and databases -- Miscellaneous -- Summary and recommendations
Keywords: DRUG INDUSTRY STANDARDS